Efficacy and safety of premixed insulin analogs in Asian patients with type 2 diabetes: A systematic review. Issue 4 (31st March 2017) - Sheu, Wayne H‐H; Ji, Linong; Lee, Woo Je; Jabbar, Abdul; Han, Jeong Hee; Lew, Thomas
Abstract: Aims/Introduction: The primary aim of this systematic review was to provide an overview of the efficacy and safety of premixed insulin analogs in Asians, specifically East Asians, with type 2 diabetes. Material and Methods: The MEDLINE, Embase, Cochrane Library and ClinicalTrials.gov databases were searched from 1 January 1995 to 26 November 2015. Randomized controlled trials involving East Asians with type 2 diabetes treated with any premixed insulin analog were included. Major comparator treatments were basal insulin and basal–bolus insulin. Comparisons were also made between East Asian and Caucasian patients. The primary efficacy outcome was glycated hemoglobin change from baseline to end‐point. The primary safety outcome was the incidence of hypoglycemia. Results: A total of 21 studies were included; most ( n = 14) were carried out in China or Japan. The duration of treatment ranged from 12 to 48 weeks. The glycated hemoglobin mean/least squares mean change from baseline to end‐point after treatment with premixed insulin analogs ranged from −0.12 to −4.2% (improvement was generally more pronounced with insulin initiation vs intensification). The incidence of hypoglycemia ranged from 8.3 to 72.0% in most studies, with the variability reflecting the definition of hypoglycemia used. Efficacy and safety outcomes for premixed insulin analogs were generally similar to those for basal or basal–bolus insulin. Limited evidence suggests that dosing, efficacy and safety profiles might differ slightly between East Asian and Caucasians receiving premixed insulin analogs. Conclusions: These results support the current use of premixed insulin analogs for managing East Asian patients with type 2 diabetes. Abstract : This systematic review provides an overview of the efficacy and safety of premixed insulin analogs in Asians, specifically East Asians, with type 2 diabetes. The results from 21 randomized‐controlled trials included in the review indicate that premixed insulin analogs can be a simple and effective means of treating type 2 diabetes in East Asians, with a safety profile that is generally similar to that of basal and basal‐bolus insulin.